Peranan Kepemimpinan Manajemen Pendidikan dalam Sekolah : (Studi Kasus di MTS Tarbiyatul Islamiyah Ciputat Hilir) - Ujang Ruslandi; Istikhori Istikhori; Asep Rizkiyana (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to examine the role of educational management leadership in improving the quality of education in schools. In the context of education, school leadership has a significant influence on managing and developing a conducive school environment. Three research questions addressed in this study are: (1) the role of the school principal in managing education, (2) leadership strategies in creating a conducive school environment, and (3) the impact of leadership on the quality of education. The research method employed is a qualitative approach, with data collection through interviews, observations, and document studies. The results indicate that effective leadership, such as implementing participatory leadership, fostering a positive culture, and utilizing technology in management, can enhance teachers' competencies and students' learning outcomes. The study also finds that principals who successfully create a positive school culture contribute to increasing motivation and performance among all school members.